Ageing-dependent properties of ZnPc/C60 photovoltaic devices - Kazukauskas, V; Arlauskas, A; Pranaitis, M; Lessmann, R; Riede, M; Leo, K (2010)
The ZnPc/C60 solar cells with a reasonable energy conversion efficiency of -1.5% were investigated. The samples were aged for 1269 hours upon illumination by the blue LED with peak emission at 475nm. Upon ageing, the devices have shown a strong and fast degradation of the efficiency, short circuit current and of the fill factor within several hours followed by a much slower decrease thereof. The carrier mobility dependences on electric field strength at different temperatures were measured by the Charge Extraction by Linearly Increasing Voltage method. The observed drop of device current cannot be explained be only mobility decrease. The increase of the effective barrier height by about 0.1eV from -0.55eV up to -0.65eV was observed in the aged samples. Meanwhile, thermal activation energy values of the electrical conductivity grew from about 0.28eV prior to degradation up to about 0.34eV after ageing. © 2010 - STC "Institute for Scientific Cruystals".